SINERGI ANTARA AGAMA DENGAN NEGARA MENUJU PROSES NEGARA MADANI - Kamilia Hamidah (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2012)
The ongoing debate over the different concept between secular state and fundamentalist state is still visible from the grass-root to the elite actors either as a discourse or as practical politics. In fact these problems commonly escalate into more violence conflict which is driven by former colonial power. An attempt to prevent the difference between the two is by proposing the concept of ideal state known as Civil Society, though these concepts it tries to synergize between state and religion. Theoretical as well as historical analysis is made to support the hypothesis. Although still on process, but at least this will be the temporary attempt to keep the stability within the society.